Seafoods: (Chapman and Hall, 1994)
This book is divided into three sections such as: the chemistry of seafood components proteins, lipids, flavorants; describes the quality of seafoods with respect to their freshness, preservation, microbiological safety and sensory attributes; the final section of the book summarizes further processing of raw material, underutilized species and processing discards for production of value added product